Pengaruh Pijat Bayi Terhadap Peningkatan Berat Badan Pada Bayi Umur 3-6 Bulan Di Puskesmas Uluan Kabupaten Toba Tahun 2023 - Winda Sepline Sirait; Nopalina Suyanti Damanik; Siska Suci Triana Ginting; Ariska Fauzianty (Jurnal Siti Rufaidah, 2024)
Babies have three needs that must be met by parents, namely physical-biological needs which are useful for brain growth, sensory systems and motor skills. Interpersonal and intrapersonal emotional intelligence through the need for affection, as well as the need for stimulus or stimulation to improve the working mechanisms of the sensory and motor systems. The most important thing in a child's growth and development is stimulation (Maharani, 2017). This study aims to analyze the effect of baby massage on weight gain in babies aged 3-6 months at the Uluan Community Health Center, Toba Regency in 2023. In this research, researchers used a quasi-experiment with a non-equivalent control group design to compare the results of health program interventions. in a similar control, but not necessarily the same group (Zulkarnain, 2018) Statistical test using Microsoft Excel and Paired Test to test differences in dependent data (dependent samples). The error rate or significance level (a) used is 0.05 with a confidence interval (CI) of 95% (Hardani, 2020). Based on the research results. Based on the results of statistical tests using Chi-Square, it was obtained that Based on the results of statistical tests using the paired t test, t = 6.610. Because t count (6.610) > t table (2.0345), HO is rejected and Ha is accepted. This shows that there is an influence of baby massage on increasing postpartum mothers regarding breast care with smooth breast milk production in Jatimulyo Village, Serdang Bedagai Regency in 2023